An Analysis of Prevention and Cure of Mental Disorder (International Journal of Food and Nutritional Sciences, 2022)
Even with optimum treatment and access to resources, modelling studies indicate that less than 30% of the burden of mental illnesses may be avoided. This emphasizes the need of reducing the prevalence of mental illnesses by implementing evidence-based preventive methods and policy changes. The argument for prevention is presented in this cross-journal article collection by highlighting proven efforts, as well as possibilities and goals for the prevention of mental illnesses in early life, the workplace, and at the population level. These articles include systematic and narrative reviews that outline the evidence basis for preventive methods, as well as commentary and debate to encourage discussion and reconsideration of preventative initiatives. Governments and funding organizations are hesitant to engage in research and policy action that may take several years to show benefits, which is a barrier to increasing preventive research. The argument for the cost-effectiveness of mental disorder prevention must be made forcefully, and new cross-disciplinary, intersectional initiatives and policies for mental illness prevention throughout the lifetime must be created.